COMPARISON STUDY OF CONVENTIONAL AND BIM BASED APPROACH IN ESTIMATING THE CONSTRUCTION COST OF SUBSIDIZED HOUSING - Muqsi, Reza Hayyu (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2024)
BIM has been wide used the achieve and effective and productive construction. Construction technology is one of the construction methods to increase productivity. Stakeholders are required to complete the project in a short time and with optimal results. One way to improve performance effectiveness is to apply the Building Information Modeling (BIM) method to quantity calculation work in order to increase work effectiveness. This study aims to compare the conventional and BIM methods. The object of this research is subsidized housing in Central Java. In the project completion process, the calculation of the volume of the roof, walls and floor uses the conventional method. Then an evaluation was carried out using the BIM method and a comparison was made between the BIM method and conventional methods. Between the two methods, the BIM method has an average accuracy rate that is better than the manual method. The results of the study show that the comparison of the cost of subsidized housing that is measured by BIM and conventional has a significant difference. Comparison of the total budget plan using the Building Information Modeling method is lower than the conventional method, namely the difference more than 1 billion.